Development of GHz Optoacoustic lenses for sub-optical resolution imaging - Yao, Mengting (2024)
Brillouin light scattering (BLS) and time-resolved Brillouin scattering (TRBS) based imaging are new techniques used for imaging and characterizing cells. These methods enable the observation of elasticity-related contrast with optical resolution and label-free operation. Phonon microscopy is a process that can detect Brillouin light scattering (BLS) using laser-generated coherent phonon fields. This approach is particularly appealing for imaging because, at GHz frequencies, the phonon wavelength is sub-optical (approximately hundreds of nm). Previous research has shown that an axial resolution up to 10 times higher than that of the optical system used for the measurements can be achieved. However, the lateral resolution is still limited by the optical systems.